Extraction of Chitin From Shrimp Shell by Successive Two-Step Fermentation of Exiguobacterium profundum and Lactobacillus acidophilus - Xie, Jingwen; Xie, Wancui; Yu, Jing; Xin, Rongyu; Shi, Zhenping; Song, Lin; Yang, Xihong (Frontiers in Microbiology, 2021)
As an environmentally friendly and efficient method, successive two-step fermentation has been applied to the extraction process of chitin. To screen out the microorganisms for fermentation, a protease-producing strain Exiguobacterium profundum and a lactic acid-producing Lactobacillus acidophilus were isolated from the traditional fermented shrimp paste. Chitin was extracted by successive two-step fermentation with these two strains, and finally 85.9% ± 1.2% of protein and 95% ± 3% of minerals were removed. The recovery and yield of chitin were 47.82% and 16.32%, respectively. Fourier transform infrared spectroscopy, X-ray diffraction and scanning electron microscopy were used to characterize the chitin. The crystallinity index was 54.37% and the degree of deacetylation was 3.67%, which was lower than that of chitin extracted by chemical method. These results indicated that successive two-step fermentation using these two bacteria can be applied to the extraction of chitin. This work provided a suitable strategy for developing an effective method to extract chitin by microbial fermentation.